2014
DOI: 10.1007/s40279-013-0139-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Maximal or Peak Oxygen Uptake from Ratings of Perceived Exertion

Abstract: Maximal or peak oxygen uptake (V˙O2 max and V˙O2 peak , respectively) are commonly measured during graded exercise tests (GXTs) to assess cardiorespiratory fitness (CRF), to prescribe exercise intensity and/or to evaluate the effects of training. However, direct measurement of CRF requires a GXT to volitional exhaustion, which may not always be well accepted by athletes or which should be avoided in some clinical populations. Consequently, numerous studies have proposed various sub-maximal exercise tests to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 73 publications
1
49
0
4
Order By: Relevance
“…Given that the HR response can be disrupted, and has technological requirements, it may be that using RPE during standard warm-up activities is an even more simple approach, as it has already been shown to be a useful strategy for predicting VO 2 max. 43 Just as sRPE has been shown to be a useful method for tracking the intensity of exercise, the process of systematically asking the athlete "how do you feel" holds the potential for monitoring the response to training. Steven Seiler has related the "hair in the cereal" story of observing athlete behavior at the breakfast table.…”
Section: The Presentmentioning
confidence: 99%
“…Given that the HR response can be disrupted, and has technological requirements, it may be that using RPE during standard warm-up activities is an even more simple approach, as it has already been shown to be a useful strategy for predicting VO 2 max. 43 Just as sRPE has been shown to be a useful method for tracking the intensity of exercise, the process of systematically asking the athlete "how do you feel" holds the potential for monitoring the response to training. Steven Seiler has related the "hair in the cereal" story of observing athlete behavior at the breakfast table.…”
Section: The Presentmentioning
confidence: 99%
“…Thus, in the meta-analysis by Chen et al among healthy subjects [36], RPE was found to be significantly correlated with several physiological parameters usually considered in the determination of the first VT such as VO 2 (r = 0.63), ventilation (r = 0.61) and blood lactate levels (r = 0.57). A more recent review performed by Coquart et al [37] concluded that the individual relationship between RPE and VO 2 (RPE/VO 2 ) can be used to predict VO 2 max (or VO 2 peak) from data measured during submaximal exercise tests.…”
Section: Discussionmentioning
confidence: 99%
“…Besides being highly correlated with physiological variables (i.e. blood lactate, heart rate, oxygen uptake) [2][3][4], RPE has shown to be a useful tool to prescribe exercise intensity in the estimation-production paradigm [4,5]. Furthermore, linear regression of submaximal RPE values vs exercise intensity (e.g., 9-17 RPE of 15-point Borg Scale) can be used to accurately predict maximal oxygen uptake (VO 2 max) [4,5], preventing the need of maximal efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, one can expect that exercise duration until exhaustion be predicted by submaximal RPE values [8,10,11]. However, in incremental exercise the accuracy of the prediction of VO 2 max can be better when extrapolating the submaximal RPE (RPE ≤ 17) to RPE19 in comparison to RPE20 [5,12]. It may be suggested that the predictions are better when RPE = 19 is used, since previous researches have already shown that an RPE = 19 is more commonly reported as the feeling of exhaustion/maximal functional capacity [9,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation